PENGARUH PERSEPSI MAHASISWA FKIP TERHADAP MINAT MENJADI GURU - Iba Gunawan; Andayani Andayani (FKIP, Universitas Banten Jaya, 2022)
This study aims to find out how students perceive interest in becoming a teacher and to find out whether there was an influence from student perceptions on interest in becoming a teacher for students in the faculty of teacher training and education at the University of Banten Jaya 2017-2020. The population in the study were 275 students. Determination of the sample using the formula according to Suharsimi Arikunto (2013) by taking 40% of the population as many as 110 students who became the sample. This research was processed using a simple regression technique. The results of this study indicate that the t-test between students’ perceptions of interest in becoming a teacher has a significant influence.